Kajian Teologi Tentang Peranan Kepala Keluarga Kristen dalam Usaha Menciptakan Kebahagiaan - Sinaga, Hendry (Sekolah Tinggi Agama Kristen Diaspora Wamena, 2022)
Family happiness is something that every married couple looks for, hopes for, and looks forward to. But the reality is completely different, how many Christian married couples are far from happy. This of course raises the question of why many Christian families do not experience happiness. So many Christian husbands do not understand their role as head of the family so that their wives and children do not enjoy family happiness. It is God who established the family institution, and God has also established the functions and roles of husband and wife. Every husband and wife who carries out their respective roles in the family, the family will be happy. On the other hand, if the husband and wife do not fulfill their role, this family will suffer. The purpose of this paper is for every head of a Christian family to understand his role based on what is written in the Bible so that a happy family is created. Because God established the family institution so that humans enjoy happiness. In this article, the author uses references research methods by taking data from books, journal and article related to the topics discussed. The conclusion of this paper is: The role of the head of the family greatly determines the happiness of a family. The more maximally a family head plays a role as instructed by God's word, the greater the level of family happiness. Wives and children will also carry out their roles according to God's word if the head of the family performs their roles according to God's command.AbstrakKebahagiaan keluarga adalah hal yang sangat dicari, diharapkan, dan dinanti nantikan oleh setiap pasangan suami istri, dan anak anak. Namun kenyataannya sama sekali berbeda, betapa banyaknya pasangan pernikahan Kristen jauh dari kebahagiaan. Hal ini tentu menimbulkan pertanyaan mengapa banyak keluarga Kristen tidak mengalami kebahagiaan. Begitu banyaknya para suami Kristen tidak memahami peranannya sebagai kepala keluarga, sehingga istri dan anak tidak menikmati kebahagiaan keluarga. Tuhanlah yang mendirikan lembaga keluarga, dan Tuhan juga yang telah menetapkan fungsi dan peranan suami dan istri. Setiap suami istri yang melakukakan perannya masing masing dalam keluarga, maka keluarga itu akan bahagia. Sebaliknya jika pasangan suami istri tidak melakukan peranannya, keluarga ini akan menderita. Adapun yang menjadi tujuan tulisan ini adalah agar setiap kepala keluarga Kristen mengerti peranannya berdasarkan apa yang tertulis dalam alkitab, sehingga terciptalah keluarga bahagia. Sebab sebenarnya Allah mendirikan lembaga keluarga agar manusia menikmati kebahagiaan. Dalam artikel ini penulis menggunakan metode penelitian riset pustaka dengan mengambil data data dari buku buku, jurnal, juga dari artikel artikel yang berhubungan dengan topik yang dibahas. Kesimpulan dari tulisan ini adalah Apabila suami sebagai kepala keluarga berperan aktif sesuai dengan kebenaran firman Tuhan, maka akan tercipta keluarga yang bahagia. Semakin maksimal seorang kepala keluarga berperan seperti yang diperintahkan firman Tuhan, maka semakin besarlah tingkat kebahagiaan keluarga. Istri dan anak akan melakukan juga peranan mereka sesuai firman Tuhan apabila kepala keluarga melakukan peranannya sesuai perintah Tuhan.